Pengaruh Kualitas Produk, Brand Association, Brand Image, Brand Trust, Price Dan Word Of Mouth Terhadap Keputusan Pembelian Sepatu Merk Vans ( Studi kasus pada pembelian Sepatu Sneakers merek Vans Di Infusionstore Malang ) - Luthfi Humam; Rois Arifin; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine and analyze the effect of product quality, brand association, brand image, brand trust, price, and word of mouth on purchasing satisfaction. Researchers are interested in this study because sales of Vans Sneakers at the Infusionstore are decreasing or not growing. With the existing theory, hopefully it can answer the problems that occur, the sample in this study is 73 consumers. The population of this study is in this study the population is all buyers of Vans Sneakers at the Malang Infusionstore from Mei to July 2020, which is estimated to reach 264 consumers. Based on the results of hypothesis testing, it is known that product quality, brand association, brand image, brand trust, price and word of mouth have a simultaneous effect on purchasing decisions and product quality, brand association, brand image, brand trust, price and word of mouth have a partial effect on purchasing decisions. . Keywords: product quality, brand association, brand image, brand trust, price, word of mouth, purchase satisfaction